Mobile networks and management : 8th International Conference, MONAMI 2016, Abu Dhabi, United Arab Emirates, October 23-24, 2016, Revised selected papers /: 8th International Conference, MONAMI 2016, Abu Dhabi, United Arab Emirates, October 23-24, 2016, Revised selected papers. (2017) - Unknown
No abstract available